Balloon pulmonary angioplasty for patients with chronic thromboembolic pulmonary hypertension previously operated by pulmonary endarterectomy. (28th July 2022) - Andersen, Asger; Hansen, Jacob Valentin; Dragsbaek, Simone Juel; Maeng, Michael; Andersen, Mads Jønsson; Andersen, Gratien; Mellemjkaer, Søren; Ilkjær, Lars Bo; Nielsen‐Kudsk, Jens Erik
Abstract: Balloon pulmonary angioplasty improved hemodynamics, walking distance, and World Health Organization functional class in patients with chronic thromboembolic pulmonary hypertension not eligible for pulmonary endarterectomy (Non‐PEA) and patients with persistent pulmonary hypertension after PEA (PEA). More mild complications were observed in PEA‐ compared to Non‐PEA.